A sphingosine kinase 2-mimicking TAT-peptide protects neurons against ischemia-reperfusion injury by activating BNIP3-mediated mitophagy. (15th December 2020) - Chen, Jia-Li; Wang, Xin-Xin; Chen, Lei; Tang, Jie; Xia, Yun-Fei; Qian, Ke; Qin, Zheng-Hong; Waeber, Christian; Sheng, Rui
Abstract: We have previously shown that sphingosine kinase 2 (SPK2) interacts with Bcl-2 via its BH3 domain, activating autophagy by inducing the dissociation of Beclin-1/Bcl-2 complexes, and that a TAT-SPK2 peptide containing the BH3 domain of SPK2 protects neurons against ischemic injury. The goals of the present study were to establish the functional significance of these findings, by testing whether TAT-SPK2 was effective in a mouse model of ischemic stroke, and to explore potential underlying mechanisms. Mice were administered with TAT-SPK2 by intraperitoneal injection before or after transient middle cerebral artery occlusion (tMCAO). Infarct volume, neurological deficit and brain water content were assessed 24 h after reperfusion. Mitophagy inhibitor Mdivi-1 and BNIP3 siRNAs were used to examine the involvement of BNIP3-dependent mitophagy in the neuroprotection of TAT-SPK2. Mitophagy was quantified by immunoblotting, immunofluorescence and electron microscopy. The interaction between TAT-SPK2 and Bcl-2, Bcl-2 and BNIP3 was detected by co-immunoprecipitation. In the tMCAO model, pre-treatment with TAT-SPK2 significantly reduced infarct volume, improved neurological function and decreased brain edema. Neuroprotection by TAT-SPK2 was still seen when the peptide was administered 3 h after reperfusion. TAT-SPK2 also significantly improved functional recovery and reduced long-term brain atrophy of the ischemic hemisphere 30 days after administration. Our studies further showed that TAT-SPK2 directly binds to Bcl-2 and disrupts Bcl-2/Beclin-1 or Bcl-2/BNIP3 complexes to induce mitophagy. These results suggest that TAT-SPK2 protects neurons against ischemia reperfusion injury by activating BNIP3-mediated mitophagy. Agents exploiting this molecular mechanism are potential candidates for the treatment of ischemic stroke. Graphical abstract: Proposed model illustrating how the TAT-SPK2 peptide protects against cerebral ischemia-reperfusion. Under normal conditions, BNIP3 and Beclin1 interact with Bcl-2 via its BH3 domain to decrease mitophagy or autophagy activity. A TAT-SPK2 peptide containing the BH3 domain of SPK2 can penetrate into neuron and bind to Bcl-2. TAT-SPK2 then disrupts the interaction between Bcl-2 and BNIP3 and between Bcl-2 and Beclin1 to induce mitophagy. BNIP3 mediated mitophagy then contributes to the neuroprotection of TAT-SPK2 against cerebral ischemia/reperfusion. Image 1 Highlights: TAT-SPK2 peptide protects against cerebral ischemia/reperfusion neuronal injury both in vivo and in vitro . TAT-SPK2 directly binds to Bcl-2 and disrupts the Beclin-1/Bcl-2 complex and BNIP3/Bcl-2 complex to induce mitophagy. TAT-SPK2 peptide may become a potential candidate for the treatment of ischemic stroke.